Permendag Analysis Number 18 year 2021 Related to the Sale and Purchase of Imported Used Clothing Trade - Elfrida Ratnawati Gultom; Ibrahim Satyanegara (LEGAL BRIEF, 2022)
Buying and selling imported used clothing is a form of transaction with clothing objects from outside Indonesia and mostly carried out by the public. Meanwhile, the Government has banned the sale and purchase transaction of imported used clothes because one of the activities violates and greatly deviates from the applicable laws and regulations. The import trade itself has also been regulated in "Article 2 paragraph (3) PERMENDAG Number 18 of 2021 concerning Exported and Imported Goods." This imported used clothing is included in the category of dangerous goods because it has been bought and sold freely and there is no strict screening beforehand. Based on the description above, the purpose of this research is to discuss the implementation of the Indonesian Minister of Trade Regulation on the trade of imported used clothes. Referring to the subject matter, How does “PERMENDAG No. 18 of 2021 concerning Exported and Imported Goods" can overcome the ban on trade in imported used clothes? and whether PERMENDAG No. 18 of 2021 concerning Exported and Imported Goods is sufficient to be the basis for banning the trade of imported used clothes? The method used in this study was normative law, using a collection technique of a literature review of primary legal materials, secondary legal materials, and tertiary legal materials. This study was carried out through systematic preparation and also analysis with theories obtained previously in a prescriptive manner. The results of this study indicate that regulations regarding the activities of buying and selling imported used clothing have been made and regulated in “PERMENDAG No. 18 of 2021 concerning Exported and Imported Goods” clearly stipulates that using imported clothes are prohibited into the territory of the Republic of Indonesia because they have an adverse effect on people's health and economy. The direct impact of selling imported used clothes is very detrimental to the community itself, particularly to the health and economy of the community.